Accountants as Pillars of Transparency: Strengthening Constitutional Law through Tax Law Enforcement in the Digital Era - Asri, Ardison; Istianingsih, Istianingsih (Greenation Research & Yayasan Global Resarch National, 2024)
Tax law enforcement is a critical element in supporting the financial stability of the state and upholding constitutional principles in Indonesia. In an era of rapid digital transformation, challenges such as tax avoidance by multinational entities and high-income individuals have become increasingly complex, requiring innovative and collaborative solutions. This study highlights the strategic role of accountants as key pillars in fostering fiscal transparency, enhancing accountability, and upholding constitutional supremacy as mandated by Article 23A of the 1945 Constitution of Indonesia. Accountants act as guardians of financial reporting integrity, ensuring compliance with tax regulations and detecting and preventing tax manipulation through the application of advanced technologies. Using a Systematic Literature Review (SLR) approach, this study identifies the significant contributions of accountants in improving tax compliance and reinforcing the implementation of constitutional principles such as justice, transparency, and accountability. The findings suggest that integrating constitutional law knowledge into accounting education, providing training in artificial intelligence-based technologies, and fostering collaboration between accounting associations and government authorities are essential steps to address the challenges faced. This research offers practical recommendations to strengthen the role of accountants in tax law enforcement, creating a more equitable, transparent, and constitutionally aligned taxation system.